LOGICAL FUNCTION ANALYSIS IN JAKARTA POST NEWSPAPER OF EDITORIAL AND NEWS TEXT - Uswar, Yenita; Harahap, Dina Irmayanti (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2022)
Logical Function is a function related to the logical relationship between one clause and another, including two aspects, namely interdependency relations and logico-semantic relations. This study demonstrated the clause complexity of the transcript of two different texts with a similar subject matter, news and editorial text from the Jakarta Post Newspaper, such as, logical function, coordination (parataxis) and subordination (hypotaxis). The method of this study highlighted the analysis of qualitative research on the issue of clause complexity based on the perspective of Systemic Functional Linguistics (SFL) in the two different texts. SFL allows the analyst to shed light on interaction with the social context to imbue texts with the meanings expressed. The results of the study show that taxis in logical function analysis of News and Editorial Text apply two taxis, they are parataxis and hypotaxis. Hypotaxis is dominantly used in both text,  85.71% in Editorial and 89.65% in News. The proportion of the dominant hypotaxis in News text was 37.93% and in Editorial 33.33%.